JURISPRUDENCE AND SOCIAL STUDY OF MARWIAT-E-SAHABIYAT RELATED TO FAMILY MATTERS - Zobia Sarwar; Dr. Mahmood Ahmad (Journal of Religion and Society, 2025)
From the beginning of the Qur'an to the present era, the services rendered by the women of Islam in the field of education and teaching, or in the field of authorship and compilation, are praiseworthy and unforgettable. It can be said with complete trust and confidence that to ignore the scholarly services of women in Islam is to erase a bright chapter of history from the pages of existence. Since Islam has ordered men and women equally in terms of getting education, women are not behind men in the field of knowledge. There is also an argument that in the first century of Hijri, a large group of women. The great scholars have testified that he is a jurist.The ancient traditions of Islam are preserved and protected in Islamic literature even today. While Western civilization and social styles are having a profound impact on Islamic societies like the whole world. The importance of family is above all in Islamic teachings, prophetic training, behavior of Companions and social formation. In Islamic history, although women achieved distinction in different positions, but the wives of Mutharat Tayyabat and Akbar Sahabiyat are a composite of all these positions and their religious, moral, social and academic achievements can be a good example for Muslim women and all the social and Blood can protect against dangers. Keywords: Islamic History, Female Companions, Traditions, Civilization, Achievements